Emerging Technologies for Electric and Hybrid Vehicles
In a world where energy conservation, environmental protection and sustainable development are growing concerns, the development of electric vehicle (EV) and hybrid EV (HEV) technologies has taken on an accelerated pace. This collection entitled "Electric and Hybrid Vehicles" invites articles that address the state-of-the-art technologies and new developments for EVs and HEVs, including but not limited to energy sources, electric powertrains, hybrid powertrains, energy management systems, energy refueling systems, regenerative braking systems, system integration, system optimization and infrastructure. Articles which deal with the latest hot topics for EVs and HEVs are particularly encouraged such as advanced lithium-ion batteries, ultracapacitors, energy-efficient motor drives, bidirectional power converters, integrated-starter-generator systems, electric variable transmission systems, on-board renewable energy, inductive or wireless charging technology, and vehicle-to-grid technology. As the impact of the use of EVs and HEVs on our daily lives is utmost important, articles which deal with the relationships between the use of EVs or HEVs and the energy, environment and economy would be of particular interest.